Bulk Scattering Approximations for Collimated Light Transmitted through Paper - Chen, Tenn Francis (University of Waterloo, 2009)
Paper is a complex fibrous material whose production involves substantial amounts of natural and industrial resources. To reduce its manufacturing costs, the pulp and paper industry often employs optical technology such as high sensitivity laser sensors used to measure physical parameters like thickness and opacity. More recently, computer simulations of paper optical properties are also being used to accelerate the research cycle required to the development of new types of paper. In these simulations, the bulk scattering of paper is usually approximated by analytical formulas, notably the Henyey-Greenstein function. In this work, we qualitatively investigate the degree of accuracy of such approximations with respect to collimated light. More specifically, an experimental set-up was devised to record the transmission of red and green HeNe lasers through different paper samples. The measured data was compared with data obtained using the Henyey-Greenstein function and data obtained using an alternative exponentiated cosine function. The comparisons are used to qualitatively assess the degree of accuracy of the bulk scattering approximations provided by both functions. This work closes with a discussion on the practical implications of our findings for the modeling of paper optical properties.
Keywords: Paper; Laser; Transmission; Approximation; Computer Science